BIOCHEMICALLY ASSESSED PATHOLOGICAL ACTIVITY OF ORAL CANDIDA IN DENTURE AND NON DENTURE WEARERS - Ghani, Fazle; Chughtai, Muhammad Ali; Shah, Syed Akram (Journal of Postgraduate Medical Institute, 2011)
Objective: To assess the candida activity through recording pH changes in candida selective mediuminoculated with standardized dilution salivary samples obtained from dentures wearers and non denturewearers.Methodology: A Cross Sectional, Comparative study during March-September 2007 was conducted atKhyber College of Dentistry Peshawar and Zoology Department, University of Peshawar (Pakistan).Usinga structured proforma, data were collected from 100 subjects (50 DWs and 50 NDWs). Stimulated salivarysamples were collected from each subject. One ml of standard dilution saliva was mixed with 4 ml sterileliquid candida-selective medium. The extent of candida activity was then determined, biochemically,° through change in pH of the medium 24 hrs after inoculation and incubation at 37 C. The influence ofage, gender, socioeconomic status, smoking habits, medication-use, oral-hygiene maintenance method,denture-plaque level, and level of salivary function was also investigated.Results: Pathological candida activity was seen both in DWs and NDWs. However, it was significantlyhigher in DWs (p value = 0.00) with mean pH decrease of 1.9 as compared to 0.8 in NDWs. Except age,the effect of gender, socioeconomic status, medications, oral hygiene maintenance on the oral candidaactivity was insignificant both within and between groups.Conclusion: Not-with-standing the varying effect of other variables, denture-wearing significantlyenhanced pathogenic activity of oral candida. The importance of meticulous oral and denture hygienemaintenance and rest to denture-supporting tissues is re-emphasized.